BAND COMBINATION SIMILARITY INDEX USING MULTISPECTRAL LANDSAT IMAGES FOR MANGROVES MONITORING - Nur Hazimah Nordin (Tesis)
This research analyzes the ability of Content Based Image Retrieval (CBIR) System to efficiently monitor mangrove ecosystems with precision. The objective of this research is to tackle the challenge of creating a reliable and automated system to effectively monitor mangrove ecosystem with precision.